FREQUENCY DOMAIN ANALYSIS OF CONSUMER CONFIDENCE, INDUSTRIAL PRODUCTION AND RETAIL SALES FOR SELECTED EUROPEAN COUNTRIES - (:unkn) unknown (VILNIUS GEDIMINAS TECH UNIV, 2011)
This paper examines the relationship between consumer confidence, economic growth and retail sales for selected countries employing frequency domain analysis. Our methodology includes the causality test developed by Breitung and Candelon (2006) which improves the methodology of Geweke (1982) and Hosoya (1991). We focus on the causality tests across frequency bands as well as the usual Granger causality tests. Especially for the emerging countries the causality goes from the economic growth to consumer confidence but not vice versa. This argument basically supports the findings of Gunes and Uzun (2010) as well as Balkyte and Tvaronaviciene (2010), which claim that in emerging countries consumers are not able to trigger the economic growth with their confidence due to their subsistence level of income. Besides, causality from consumer confidence to retail sales, which is a proxy for the consumer expenditures, is detected. As in Basdas and Celik (2010), we also obtain significant differences whenever the frequency domain causality tests are employed instead of usual Granger causality tests in time domain.
Keywords: consumer confidence; causality analysis; frequency domain analysis; Breitung and Candelon test; SENTIMENT; EXPECTATIONS